Practical Theology as Public Ethics: Faith Communities, Gender-Based Violence, and the Reproduction of Patriarchal Norms in South Africa - Hundzukani P. Khosa-Nkatini; Mpho Johannes Ndaka (UIN Sunan Gunung Djati Bandung, 2025)
This article examines the role of practical theology in responding to femicide and gender-based violence (GBV) in South Africa, one of the countries with the highest rates of violence against women globally. The study aims to analyze how practical theology can function as a reflective–transformative framework to challenge religious patriarchy, to build victim-centered pastoral praxis, and to promote prevention and social transformation through the engagement of faith communities. The research employs a qualitative approach with an exploratory–descriptive design, combining thematic analysis of interviews with church leaders and local religious actors with a critical review of literature on practical theology, African feminist theology, and faith-based intervention studies. The findings reveal three main points. First, patriarchal theological language and interpretation operate as a symbolic architecture that normalizes violence through the sacralization of family unity, the privatization of suffering, and the spiritualization of women’s sacrifice. Second, church pastoral praxis remains ambivalent: it can provide an initial space of protection for survivors, yet it can also prolong risk when it lacks victim-safety standards such as do no harm, security-based confidentiality, informed consent, and cross-sector referral mechanisms. Third, faith community engagement proves most transformative when practical theology operates as public ethics—through relational education on respect, consent, and non-violence; the formation of men and young men; bystander interventions; gender justice advocacy; and interdisciplinary collaboration with health, legal, and social services—supported by traceable impact indicators. This article argues that practical theology holds strategic capacity to transform churches from ambivalent normative institutions into public moral actors that contribute concretely to GBV prevention, survivor protection, and social norm change. In terms of originality, the study offers a conceptual contribution by positioning practical theology as a bridge between faith, survivors’ lived experiences, and measurable social transformation within the South African context.